Penyuluhan Pengelolaan Keuangan Keluarga Anggota Kelompok Tani "Sido Dadi" Desa Puntik Tengah, Kecamatan Mandastana, Kabupaten Barito Kuala - Julkawait; Mukhlisah, Nurul; Nikmah, Nailiya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service was carried out to improve the financial literacy of the "Sido Dadi" Farmer Group members in Puntik Tengah Village, Mandastana District, Barito Kuala Regency. The main problem partners face is the low understanding of family financial management, especially in financial recording and budgeting, as well as irregular income. The purpose of this community service activity is to improve the financial literacy of members of the "Sido Dadi" Farmer Group so that they can better manage family income and expenses. Equipping participants with practical skills in making a family budget and managing income fluctuations. As well as teaching the importance of saving and investing for the future, so that families have adequate financial reserves. Counseling and mentoring activities are carried out through lecture methods, budgeting simulations, and implementation assistance in the field. The results of counseling and mentoring in family financial management, participants showed a significant increase in understanding of the principles of financial management, such as budgeting, recording expenses, and income, and the importance of saving and investing.